Indifferent and Eurosceptic: The motivations of EU-only abstainers in the 2019 European Parliament election. (November 2021) - Schäfer, Constantin
Despite the dramatic voter turnout increase in 2019, the participation level in European Parliament elections is still considerably lower than in national elections. How can we explain this persistent 'Euro gap'? This article analyses the motivations of citizens who participate in national but not in European electoral contests, the so-called 'EU-only abstainers'. The empirical analysis based on the EES 2019 voter study reveals that EU-only abstention is driven by low levels of general political interest and EU-specific political sophistication, as well as by distrust towards EU institutions. Therefore, the Euro gap results from the widespread perception that there is 'less at stake' during EP elections, but it is also an aggregate-level consequence of individual Eurosceptic attitudes. These findings have important implications for our understanding of present-day European elections and the debate between the two most common theoretical approaches in EP election research.